The Effectiveness of RME in Improving Numeracy of Class V Students in the Teaching Campus Program - Nur Akfina; Ageng Triyono; Titi Anjarini (Journal of Instructional Mathematics, 2025)
The numeracy skills of students in the schools studied are still low, although numeracy is a fundamental skill needed to understand mathematical ideas. This study aims to examine the effectiveness of Realistic Mathematics Education (RME) in improving numeracy performance among fifth grade students in elementary schools who receive support from the national teaching placement program in Kebumen Regency. This study used a pre-experimental approach with a one-group pretest-posttest structure, involving all fifth graders selected through purposive sampling who took part in contextual learning activities related to daily living situations. Numeracy ability was measured using official government instruments provided before and after the intervention. The results showed a clear improvement in numeracy performance and highlighted increased student participation and a more positive response to math teaching when based on a real-world context. The study concludes that RME contributes to strengthening students' motivation, logical reasoning, and problem-solving skills, and is therefore recommended as an instructional approach to support the development of essential mathematics competencies in primary schools.